Tidal and subtidal hydrodynamics and energetics in a constricted estuary. (5th February 2017) - Zarzuelo, Carmen; López-Ruiz, Alejandro; Díez-Minguito, Manuel; Ortega-Sánchez, Miguel
Abstract: The dynamics of coastal plain estuaries are mainly associated with variable tidal forcing and local winds in combination with bathymetric complexity and coastline irregularity. Specific features, such as constricted areas, can potentially affect and energize the hydrodynamics of these types of systems. Particularly, tidal range and tidal currents can be significantly amplified where the incoming tidal wave becomes constricted. In this work, the impact of a narrow constriction on a mesotidal estuary was analysed at tidal and subtidal time scales. Tidal hydrodynamics, energy fluxes and energy dissipation were determined for the entire Cádiz Bay (southwestern Spain) using the Delft3D numerical model. Field observations were used to analyse tidal propagation and energy dissipation along the bay constriction and to calibrate and test the numerical model. The results indicate that the presence of the constriction transformed and distorted the tide and increased the tidal range and flow velocities along the channel, with implications on energy dissipation. The tidal currents were oriented along-channel at the central part of the constriction, although abrupt bathymetric changes at the channel inner boundary provoked a sudden rotation of the flow. Although the energy fluxes were higher for spring tides and were strongly influenced by winds, the energy dissipation was controlled by bed shear stresses and vertical dispersion. The significance of this energy dissipation was that it destabilized the water column, which resulted in a weakly stratified system with implications on water quality. At a subtidal scale, the residual water volume exchange was the result of the combined effects of the neap/spring tides, wind and waves, whereas tides were dominant at the tidal scale.